Hadith #2595 - Sahih al-Bukhari - al-Hasan al-Basri الحسن البصري (Sahih al-Bukhari)
By Allah, Al-Hasan bin `Ali led large battalions like mountains against Muawiya. `Amr bin Al-As said (to Muawiya), “I surely see battalions which will not turn back before killing their opponents.” Muawiya who was really the best of the two men said to him, “O `Amr! If these killed those and those killed these, who would be left with me for the jobs of the public, who would be left with me for their women, who would be left with me for their children?” Then Muawiya sent two Quraishi men
Grade: Sahih

Hadith #4324 - Sahih al-Bukhari - al-Hasan al-Basri الحسن البصري (Sahih al-Bukhari)
The sister of Ma’qal bin Yasar was divorced by her husband who left her till she had fulfilled her term of ‘Iddat (i.e. the period which should elapse before she can Remarry) and then he wanted to remarry her but Maqal refused, so this Verse was revealed:– “Do not prevent them from marrying their (former) husbands.” (2.232)
Grade: Sahih

Hadith #4924 - Sahih al-Bukhari - al-Hasan al-Basri الحسن البصري (Sahih al-Bukhari)
concerning the Verse: ‘Do not prevent them’ (2.232) Ma’qil bin Yasar told me that it was revealed in his connection. He said, “I married my sister to a man and he divorced her, and when her days of ‘Idda (three menstrual periods) were over, the man came again and asked for her hand, but I said to him, ‘I married her to you and made her your bed (your wife) and favored you with her, but you divorced her. Now you come to ask for her hand again? No, by Allah, she will never go back to y
Grade: Sahih

Hadith #5116 - Sahih al-Bukhari - al-Hasan al-Basri الحسن البصري (Sahih al-Bukhari)
Ma’qil gave his sister in marriage and later her husband divorced her once.
Grade: Sahih

Hadith #5117 - Sahih al-Bukhari - al-Hasan al-Basri الحسن البصري (Sahih al-Bukhari)
The sister of Ma’qil bin Yasar was married to a man and then that man divorced her and remained away from her till her period of the ‘Iddah expired. Then he demanded for her hand in marriage, but Ma’qil got angry out of pride and haughtiness and said, “He kept away from her when he could still retain her, and now he demands her hand again?” So Ma’qil disagreed to remarry her to him. Then Allah revealed: ‘When you have divorced women and they have fulfilled the term of their prescri
Grade: Sahih

Hadith #6818 - Sahih al-Bukhari - al-Hasan al-Basri الحسن البصري (Sahih al-Bukhari)
(Al-Ahnaf said:) I went out carrying my arms during the nights of the affliction (i.e. the war between `Ali and `Aisha) and Abu Bakra met me and asked, “Where are you going?” I replied, “I intend to help the cousin of Allah’s Messenger (ﷺ) (i.e.,`Ali).” Abu Bakra said, “Allah’s Messenger (ﷺ) said, ‘If two Muslims take out their swords to fight each other, then both of them will be from amongst the people of the Hell- Fire.’ It was said to the Prophet, ‘It is alright for t
Grade: Sahih

Hadith #6840 - Sahih al-Bukhari - al-Hasan al-Basri الحسن البصري (Sahih al-Bukhari)
When Al-Hasan bin `Ali moved with army units against Muawiya, `Amr bin AL-As said to Muawiya, “I see an army that will not retreat unless and until the opposing army retreats.” Muawiya said, “(If the Muslims are killed) who will look after their children?” `Amr bin Al-As said: I (will look after them). On that, `Abdullah bin ‘Amir and `Abdur-Rahman bin Samura said, “Let us meet Muawaiya and suggest peace.” Al-Hasan Al-Basri added: No doubt, I heard that Abu Bakra said, “Once whil
Grade: Sahih

Hadith #7249 - Sahih al-Bukhari - al-Hasan al-Basri الحسن البصري (Sahih al-Bukhari)
`Amr bin Taghlib said, “Some property was given to the Prophet (ﷺ) and he gave it to some people and withheld it from some others. Then he came to know that they (the latter) were dissatisfied. So the Prophet said, ‘I give to one man and leave (do not give) another, and the one to whom I do not give is dearer to me than the one to whom I give. I give to some people because of the impatience and discontent present in their hearts, and leave other people because of the content and goodness A
Grade: Sahih